Collectivism and meaning-making: A search for moderators - Daphna Oyserman; Yahan Huang; Amabel Y. Jeon (PLoS ONE, 2026)
People differ in how much they endorse collectivistic values (e.g., valuing group membership, and experiencing as essential in-group belonging, adhering to norms, and group connection). A posited behavioral consequence of valuing collectivism is that people may attempt to avoid group ruptures by actively seeking meaning in what their interaction partners say, asking themselves, “How might this make sense?” when a statement is ambiguous. Indeed, people who endorse collectivism find more meaning in ambiguous claims made by others. We investigate the robustness of this association and examine three theory-central potential moderators (communicator group membership, focus on meaning-making vs assessing accuracy, processing depth; N = 1,174). Across three experiments and in pooled analyses, higher collectivism is associated with rating ambiguous statements as more meaningful; this relationship is stronger when the communicator is from an in-group rather than an out-group, supporting the first posited moderator. We do not find support for the second moderator, perhaps due to the subtlety of our meaning vs. accuracy manipulation. And, while higher later incidental recall of communicator group membership is associated with finding more meaning in ambiguous statements, this incidental processing main effect is not consistently moderated by collectivism. Exploratory pooled analyses also suggest that people drew more meaning from ambiguous statements from a communicator who was a fellow student at their alma mater or at the rival university, rather than from a more contentious social group (their own or the rival political party). Moreover, at least just before and after a Presidential election in which Democrats were underdogs, collectivistic Republicans saw more meaning in messages from both Republicans and Democrats. Collectivistic Democrats saw more meaning only in messages from other Democrats. Our findings suggest that collectivism’s effects on meaning-making are context-dependent --group type and group boundary salience shape effect sizes. Future research should consider this interplay.